Congenital Heart Disease in New Borns and Children, Clinical Features and Management- A Review - Dr.P.Paramanantham; Dr.P.S.SathulHak (International Journal of Pharma and Bio Sciences, 2021)
Congenital heart disease / congenital heart defects are more common than anomalies of any other systems of the human body. These defects occur in-utero during the organogenesis period, particularly in 1st trimester and the congenital heart disease may occur subsequently during development of the baby due to various environmental, genetic and developmental growth of the heart upto 1 year of life and these defects or illnesses result in various clinical implications with clinical signs and symptoms for us to diagnose and give appropriate therapy. Most of the cyanotic congenital heart disease cyanosis develops at birth and some congenital heart disease particularly Fallot’s develop cyanosis late in the neonatal period. Most of the congenital heart disease respond to prostaglandin therapy, particularly this therapy is contraindicated in total anomalous pulmonary venous connection. This review explains the timing of referral of these CHD babies and children to the pediatric cardiologist and if necessary to pediatric cardiac surgeons. It is essential to know congenital heart disease forms a bulk which needs more pediatric cardiologists and pediatric cardiac surgeons. Only 200 pediatric cardiologists and 180 pediatric cardiac surgeons are available in the whole of India. Hence to give adequate care, proper identification and need for referral at an appropriate time is essential to decrease the morbidity and mortality in pediatric cardiac patients.